The life and voyages of Joseph Wiggins, F.R.G.S.; modern discoverer of the Kara Sea route to Siberia, based on his journals & letters - Johnson, Henry. (New York : E.P. Dutton & co., 1907)
"Printed in Great Britain." Mode of access: Internet.